REALITAS SOSIAL ANAK BERHADAPAN HUKUM DALAM INSTITUSI TOTAL LEMBAGA PEMBINAAN KHUSUS ANAK KELAS I MEDAN - Sinulingga, Eldinda Faridzi Rachmayani; Siregar, Hairani (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The phenomenon of children facing the law is a social reality that until now cannot be avoided and overcame by the social community, because social life has been greatly influenced by various developments in technology, culture, economy, and other factors. The purpose of this research is to explain the reasons for obtaining the status of children facing the law, the lives of children facing the law at the Class I Special Development Institution for Children in Medan, and the plans of children facing the law to build their future. This research was conducted at the Medan Class I Children's Special Development Institute involving eight informants consisting of three key informants, three main informants, and two additional informants. Using qualitative methods as the data collection techniques, with interviews, observation, and documentation by using phenomenological theory, specifically the theory by Peter L. Berger and Alfred Schutz, to be able to draw the research conclusions. The result of the research show that the cause of children obtaining legal status is linked to parenting patterns and the influence of the social environment. This research has also shown the lives of children in conflict with the law at the Special Children's Development Institution, namely undergoing a coaching program provided by the Medan Class I Special Children's Development Institution, including religious, morality, development of independence, physical/sports, and teaching-learning activities consisting of "sekolah kejar paket" A, B and C. The plan for children in conflict with the law, is to build a future for them, while aiming to eliminate the negative stigma that children in conflict with the law may experience when they return to society. Children in conflict with the law have various plans for the future, namely continuing their education, working as a form of independence in a new social environment, and become a better person.